2022
DOI: 10.3389/fpls.2022.1016737
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and synergistic activity of compounds from essential oils and their effect on detoxification enzymes against Planococcus lilacinus

Abstract: Mealybug, Planococcus lilacinus Cockerell, is a primary surface-feeding insect pest of fruit and flowering plants and also transmits plant viruses, resulting in economic crop loss. Inappropriate and recurrent use of pesticides for mealybug control results in resistance building and deleterious effects on humans and the environment. Essential oils are the most excellent choice for insecticides. Insecticidal activities of pure compounds of essential oils against P. lilacinus are not reported. The present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Nevertheless, prior research on the structural abnormalities brought on by Tagetes minuta L. oil against A. craccivora , and Plutella xylostella (Linnaeus, 1758) was scarce and substantially corroborated the current study’s findings ( Dolma et al., 2022 ; Jayaram et al., 2022 ). Also the ocimene-treated Planococcus lilacinus (Cockerell, 1905) showed multiple abnormalities on the setae, thoracic leg, and cuticle (body fluid accumulation and thickness encrustations) ( Arokiyaraj et al., 2022 ). According to findings from other authors ( Botas et al., 2017 ; Pessoa et al., 2018 ), A. aegypti and C. quinquefasciatus larvae showed modifications in the cuticle of the head, thorax, abdomen, and siphon when treated with various nanoemulsions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, prior research on the structural abnormalities brought on by Tagetes minuta L. oil against A. craccivora , and Plutella xylostella (Linnaeus, 1758) was scarce and substantially corroborated the current study’s findings ( Dolma et al., 2022 ; Jayaram et al., 2022 ). Also the ocimene-treated Planococcus lilacinus (Cockerell, 1905) showed multiple abnormalities on the setae, thoracic leg, and cuticle (body fluid accumulation and thickness encrustations) ( Arokiyaraj et al., 2022 ). According to findings from other authors ( Botas et al., 2017 ; Pessoa et al., 2018 ), A. aegypti and C. quinquefasciatus larvae showed modifications in the cuticle of the head, thorax, abdomen, and siphon when treated with various nanoemulsions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pavela [41,42] demonstrated that the binary mixtures of carvone and linalool resulted in synergistic effects on the adult mortality of Spodoptera littoralis and C. quinquefasciatus, respectively. Additionally, ocimene strongly synergized the toxicity of β-myrcene, L-limonene, geraniol, and L-menthol against Planococcus lilacinus [43]. In addition, the study of Prasannakumar et al [30] revealed that the combined use of 4-carene and α-pinene was very effective against Phthorimaea absoluta.…”
Section: Discussionmentioning
confidence: 96%
“…The bioactivity of plant oils are attributed to several components, with demonstrable insecticidal activity contained in the plant EO, especially in monoterpenes such as αpinene, α-terpinene, limonene, camphor, carvacrol, thymol, δ-3-carene, α-thujone, 1,8-cineol (eucalyptol), eugenol, and ascaridole [3,6,[9][10][11]17,57]. Although a synergism with other minor constituents is common where each oil component participates in penetration, fixation, and distribution into biomembranes [6,9,17], synergy between components of an EO might be occur between several components contained in the same oil, or between different essential oils with known biological activities [17,64,65].…”
Section: Discussionmentioning
confidence: 99%